Enhancing Prophetic Arabic Vocabulary for Understanding Al-Arba'in Al-Nawawiyah through Board Game: A Systematic Literature Review - Muhammad Anwar Ahmad; Muhammad Nur Farhan Zamziba; Hishomudin Ahmad; Ku Mohd Syarbaini Ku Yaacob (Universiti Malaysia Pahang Al-Sultan Abdullah Press (UMPSA Press), 2026)
Tier 3